2018
DOI: 10.7575/aiac.alls.v.9n.6p.192
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Literacy Practices in a University EFL Context from Multiliteracies and Multimodal Perspective: A Case Study

Abstract: This study attempts to investigate the literacy practices of EFL teaching and learning in higher education level from multiliteracies and multimodal perspective. Mixed methods were used: questionaires to the students, interviews with both teachers and students, focus group discussion with students, observation, and documents. The study was focused on the English reading and writing classroom activities. The results of the study revealed that most participating students frequently utilized on screen text and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…Less understanding toward the comprehensive conceptions of literacy might have implication to the teachers' literacy development and eventually affect to their teaching practices. Therefore, the misconception of teaching English focusing only on the English core skills should be avoided [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less understanding toward the comprehensive conceptions of literacy might have implication to the teachers' literacy development and eventually affect to their teaching practices. Therefore, the misconception of teaching English focusing only on the English core skills should be avoided [9].…”
Section: Discussionmentioning
confidence: 99%
“…Pedagogy of Multiliteracies was introduced to adapt the advancement of technology utilizing multimodality [4,[22][23][24]. Moreover, today's learners are considered as digital natives [2], and therefore, the nature of learning has shifted from print based into digitalization [9]. An additional point to emerge from this study is that teachers should follow the rapid growth of technology and adopt them in their teaching practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fukunaga's (2006) study on Japanese as foreign language learners suggested that reading animes could contribute to the development of word recognition, listening skills, pronunciation, and cultural awareness. Another study has analyzed EFL students' literacy practices in the language classroom, with special attention to the media of communication (Nabhan & Hidayat, 2018). It is reasonable to believe that foreign language literacy practices also occur in multiple contexts and involve various communication channels and semiotic resources (e.g., Nabhan & Hidayat, 2018;Rothoni, 2018).…”
Section: Research On L2 Literacymentioning
confidence: 99%
“…Another study has analyzed EFL students' literacy practices in the language classroom, with special attention to the media of communication (Nabhan & Hidayat, 2018). It is reasonable to believe that foreign language literacy practices also occur in multiple contexts and involve various communication channels and semiotic resources (e.g., Nabhan & Hidayat, 2018;Rothoni, 2018). Focusing only on the linguistic aspect would seriously undermine the complex nature of literacy.…”
Section: Research On L2 Literacymentioning
confidence: 99%